An easily ignored factor for CAN-fine particulate exposure [Letter] - Sun H; Liang M; Zheng N (Diabetes, Metabolic Syndrome and Obesity, 2019)
Hua Sun,*,1 Man Liang,*,2 Na Zheng31Department of Endocrinology, The Affiliated Hospital of Beihua University, Jilin City, Jilin 132011, People’s Republic of China; 2Department of Forensic Science, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430030, Hubei, People’s Republic of China; 3Department of Pathology, Health Science Center, Shen Zhen University, Shenzhen, Guangdong 518066, People’s Republic of China*These authors contributed equally to this workWe read with great interest the recently published article by Vasheghani et al.1 In the article, the authors showed that the prevalence of CAN was increased with prolonged duration of DM, but not the glycemic control level.View the original paper by Vasheghani and colleagues.